The Effect Of Operating Costs And Income On Performance Finance Based On Return On Asset Ratio In Broiler Companies Listed On The Stock Exchange Indonesia 2019-2024 - Febriana, Febriana Magdalena Pakpahan; Faisal Akbar (Fakultas Ekonomi Prodi Akuntansi, 2026)
The purpose of this study was to determine the effect of operational costs and income on financial performance based on the return on asset ratio in broiler chicken industry companies listed on the Indonesia Stock Exchange in 2019-2024. The research design used is an associative approach. The population in this study were 5 food and beverage companies listed on the Indonesia Stock Exchange in 2019-2024, with a sampling technique using purposive sampling, so that the research sample amounted to 30 broiler chicken industry companies listed on the Indonesia Stock Exchange in 2019-2024. In this study, the type of data used is quantitative data. The data sources used in this study were obtained from the Indonesia Stock Exchange (IDX) website. The data analysis method uses multiple linear regression analysis with SPSS.25. Based on the results of the t-test that has been carried out, it can be concluded that operational costs have a positive and significant effect on financial performance, income has a positive and significant effect on financial performance. Based on the results of the f-test, it is concluded that operational costs and income have a simultaneous effect on financial performance based on the return on asset ratio in broiler chicken industry companies listed on the Indonesia Stock Exchange in 2019-2024.